Pseudocrossidium pachygastrellum (Herzog) Broth - Suarez, Guillermo Martin (2010)
During examination of collections from ‘La Cienaga’, in the Northwest of Argentina (Sua´rez, Schiavone & Zander, 2010), certain specimens were identified as Pseudocrossidium pachygastrellum, a species in the family Pottiaceae and only recorded previously from Bolivia (Churchill, Sanjines & Aldana, 2009).